2010
DOI: 10.1111/j.1533-8525.2010.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

Race, Class, Gender, and Social Space: Using an Intersectional Approach to Study Immigration Attitudes

Abstract: This study uses an intersectional approach to predict attitudes toward immigrants by examining the intersections of race, class, gender, and social space. With data from the 2004 General Social Survey and the 2000 Census, generalized hierarchal linear modeling generates significant two-way and three-way interactions in predicting attitudes toward immigrants taking jobs, improving the economy, committing crime, and migrating to the United States. Important differences in attitudes between groups and within grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 39 publications
1
36
1
2
Order By: Relevance
“…Indeed, the conflict and contact hypotheses pertain to the dominant in-group, which is most often defined as native-born whites, while blacks, despite being native-born for the most part, are excluded as an out-group. When survey samples include sufficient numbers of non-Hispanic blacks to compare their views to those of whites, depending on the specific issue, blacks are found generally to be more liberal than whites (Buckler, Swatt and Salinas 2009; Berg 2010; Burns and Gimpel 2000; Citrin, Green, Muste, and Wong 1997; Diamond 1998; Espenshade and Hempstead 1996) or no different (Diamond 1998; Cummings and Lambert 1997). …”
Section: Research On Attitudes Toward Immigrants and Immigration Policymentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the conflict and contact hypotheses pertain to the dominant in-group, which is most often defined as native-born whites, while blacks, despite being native-born for the most part, are excluded as an out-group. When survey samples include sufficient numbers of non-Hispanic blacks to compare their views to those of whites, depending on the specific issue, blacks are found generally to be more liberal than whites (Buckler, Swatt and Salinas 2009; Berg 2010; Burns and Gimpel 2000; Citrin, Green, Muste, and Wong 1997; Diamond 1998; Espenshade and Hempstead 1996) or no different (Diamond 1998; Cummings and Lambert 1997). …”
Section: Research On Attitudes Toward Immigrants and Immigration Policymentioning
confidence: 99%
“…In some studies women favor more liberal immigration policies (Buckler, Swatt, and Salinas 2009; Chandler and Tsai 2001), but others find no difference between men and women (Berg 2009; Espenshade and Calhoun 1993; Espenshade and Hempstead 1996; Haubert and Fussell 2006; Hood and Morris 1997, 1998; Scheve and Slaughter 2001), and still others find that women favor more restrictive immigration policies (Buckler 2008; Burns and Gimpel 2000; Chandler and Tsai 2001; Hood, Morris and Shirkey 1997). Berg (2010) offers an intersectional explanation for this inconsistency by showing that social identities – specifically race, class, and gender groups – combine with one another to produce countervailing effects. Further, these identity combinations depend on the percentage of foreign-born residents in an area.…”
Section: Research On Attitudes Toward Immigrants and Immigration Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Hempstead and Espenshade 1996). Recent studies have also shown that women seem to be more concerned than men about the social integration and economic assimilation of illegal immigrants (Hughes and Tuch 2003;Berg 2010;Correia 2010;Amuedo-Dorantes and Puttitanun 2011). Women also appear to have more exclusionary reactions to immigrants coming from poor countries in Europe (Gorodzeisky 2011) and to report feeling higher levels of economic threat from immigration, while men seem to be more prone to feelings of cultural threat (Pichler 2010).…”
Section: Empirical Findings: Individual and Household Characteristicsmentioning
confidence: 99%
“…One of the most consistent predictors of a positive immigration attitude is educational status. Individuals who report higher levels of education are significantly more likely to express sympathetic views toward all immigrant groups and be comparatively open to pro‐immigrant policies than less educated groups (e.g., see Berg ; Burns and Gimpel ; Espenshade ; Hood et al ). Evidence suggests that education has a similar impact on individuals in European countries as well (Ceobanu and Escandell ; Hainmueller and Hiscox ).…”
Section: Personal and Social Identitymentioning
confidence: 99%